Developmental trajectories in mental health through adolescence and adulthood: does socio-economic status matter? - Christine Leonhard Birk Sørensen; Oleguer Plana-Ripoll; Ute Bültmann; Trine Nøhr Winding; Pernille Bach Steen; Karin Biering (Epidemiology and Psychiatric Sciences)
Abstract Aims This study aims to examine the different aspects of socio-economic status (SES) patterns in mental health from adolescence into adulthood by investigating the mean, prevalence, cumulative incidence and trajectories of several mental health measures, including depressive symptoms, mental disorder diagnosis and medication use. The different aspects of SES are investigated through the measures of subjective social status (SSS) in school, SSS in society, income and parental educational level.